Perancangan Prototipe Untuk Pengujian Karakteristik Solar Photovoltaic (SPV) Pada Cuaca Kota Pekanbaru - Wallsman Lamtota Nainggolan; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Solar energy in the form of light emitted (radiation) to the earth can be used as the main source to produce electrical energy directly by using the solar photovoltaic function (SPV) or also called the photovoltaic effect. The electrical energy generated from this SPV is in the form of a DC voltage. The energy produced by SPV needs to be researched to understand the characteristics of SPV in different places and conditions. The research conducted was to observe the SPV characteristics for weather conditions in Pekanbaru. Sunlight that radiates on the SPV was placed at an angle of zero degrees horizontally with the surface of the earth. The method that used to obtain SPV characteristics is stand alone solar photovoltaic testing by installing a rheostat (variable resistor) at the SPV output. it's value is 0-100 Ohms which will then be shifted from the largest value to the smallest rheostat value. From the tests conducted will produce SPV characteristic parameter data and can form curves I - V and P – V. The results of real-time measurements produce data to form a characteristic curve, ISC of polycrystalline solar photovoltaic type was 1.0232 V while monocrystalline solar photovoltaic ISC was 0.92912 V. The open circuit voltage (VOC) in both types of solar photovoltaics had the same value which was 20.41 Volts. Keywords: solar energy, solar photovoltaik, rheostat, curves, stand alone